Combating stigma in autism research through centering autistic voices: a co-interview guide for qualitative research - Kaplan-Kahn, Elizabeth A.; Caplan, Reid (Frontiers in Psychiatry, 2023)
As autism has gained increased attention in the past few decades, autistic advocates have adopted the phrase "Nothing about us without us," illustrating the idea that autistic people should be centered in all conversations regarding autism. However, in a large portion of autism research, autistic people are still not meaningfully engaged throughout the research process, leading to continued stigma in research through biased methods. Thus, stigma about autism influences not only the content of autism research, but the ways in which neurotypical people conduct research alongside (or without) autistic people, ultimately resulting in less valid conclusions or research that actively harms the autistic community. One way to address this stigma is through involving autistic individuals as equal partners in the research process, such as by including autistic co-interviewers in qualitative studies of autistic people. In this perspectives piece, we will highlight the benefits of participatory research practices within qualitative research. Furthermore, we will outline methods for conducting cointerviews with autistic research partners and share insights from our experiences implementing this practice. We hope this piece provides researchers the practical resources and inspiration to continue working towards decreasing the stigma surrounding autism in research spaces.1 Here, we mean 'autistic researcher' to refer to any autistic person who is engaged in research practices, regardless of their education, training, degree, or employment.